(untitled) (KULT_online, 2009)
The edited collection Die zerstörte Stadt. Mediale Repräsentationen urbaner Räume von Troja bis Sim City (Destroyed Cities. Media Representations of Urban Spaces from Troy to Sim City) approaches a hitherto neglected topic in urban studies: the perpetual processes of de- and re-constructing the city. As conceptual relationships between the essays are not outlined in the preface, the collection forfeits its potential to systematically guide the reader through this broad academic discourse. However, its wide historical range and interdisciplinary stance provide an innovative contribution and vivid introduction to a newly evolving topic in urban studies.